Batasan Pertanggungjawaban PPAT Terhadap Ketidakabsahan Dokumen Kelengkapan Persyaratan dalam Sistem Hak Tanggungan Elektronik (HT-EL) - Buditama, Fitriya Nurmayuvita; Olii, Indah Wahyuni; Azizah, Theanya Putri (Universitas Proklamasi 45, 2024)
This research aims to analyze the limits of PPAT's responsibility for documents completing the requirements in the Electronic Mortgage System (HT-el) as well as analyze the legal protection of PPAT as the person responsible for the validity and correctness of documents in the HT-el system. The research was conducted by the authors using a normative juridical writing method with descriptive analysis with a conceptual approach and a statutory approach. The legal sources used are primary, secondary, and tertiary legal sources using literature study methods and then analyzed by the author using systematic, extensive, and comparative interpretation. The limitation of PPAT's responsibility for the HT-el system is limited to the process of making a statement letter. If PPAT has carried out its duties and procedures by the provisions then it cannot be punished by Article 51 Paragraph 1) of the Criminal Code and according to Supreme Court Jurisprudence 385/K/Pid/2006. PPATs in carrying out their profession receive legal protection, namely preventive legal protection and repressive legal protection. PPAT's preventive legal protection in carrying out each of its duties and authorities must be based on the precautionary principle. Repressive legal protection: A PPAT can make efforts to defend themselves and receive legal assistance in the form of advice, input, or assistance during the investigation process.